(untitled) (Journal of the College of Basic Education, 2022)
Design is the process of formation and innovation, i.e. collecting elements from the environment and putting them in a specific composition to give something that has a function or meaning, and some differentiate between composition and design. They are preliminary requirements to evoke feelings of enjoyment of beauty. Fabrics are one of those elements that are included in the composition of the design, as they contributed to the formation of the utilitarian and aesthetic features of art by building its growing texture and adapting to each interior design, which gives it the ability to constantly renew to formulate interior spaces with aesthetic expressions characterized by accuracy and fit with age, Which forms the aesthetics of composition in the interior design process by dealing with the interior spaces to create the appropriate atmosphere and achieve psychological comfort through the distribution and employment of the basic interior design elements: (ceilings - floors - walls - furniture and the aesthetics of its fabrics), architectural elements: (drawers - architectural openings) The elements are affected by: (light - color - ventilation - sound), complementary elements: (accessories of all kinds: vases clocks - fountains - green elements). Hence the problem, which is summarized in the following question: Does the aesthetics of fabrics play a role in the success of the content of the interior space? While the importance of the research lies in the study of the aesthetics of the fabrics, as it reflects the aesthetic and functional values ​​in the interior space, and this process serves the interior designers in making the design successful. In addition to studying the requirements for building interior space based mainly on the use of basic interior design elements and architectural and complementary elements. While the research aims to reveal the aesthetics of the fabrics and their role in the success of the content of the interior space. The research study also included the axes of the theoretical framework in which the basic and architectural elements of interior design were reviewed. As well as the research procedures represented by the research methodology based on the descriptive analytical approach. Finally, the research study ensures that the most important results and conclusions are drawn. Results : The study of the interior designer emphasized the focus on the basic and architectural elements within the design of interior spaces by relying on various design patterns, including furniture and the uses of fabrics, to build interior spaces with aesthetic expressions characterized by accuracy and fit with the times to create various design innovations through creating the appropriate atmosphere and achieving comfort Psychology that expresses the principles of maintaining life on an ongoing basis. The ability of the interior designer to determine the uses of fabrics within the interior space was achieved through the designer in order to create things that were achieved for aesthetic and utilitarian purposes at the level of interior design, which helped the designer in the success of his design work. Conclusions: The researcher provided readings through the history of interior design and architecture, and studied the various cases that practiced interior design, and shed light on the true meaning of architecture and the relationship between the exterior and interior and the elements and principles of design. With the study of space, theory and interior elements, which led to the formation of a clear vision of the state of interior design with a special focus on the methods and tools necessary to improve and develop practice. The study of the interior designer is formed to rely on the design elements within the interior design through plastic innovation or the formation of beautiful and interesting things in order to make the content of the interior spaces successful based on the aesthetics of the various design elements.